Entrepreneurship Orientation, Market Orientation and Aesthetics Innovation Mediate towards Business Performance of Sulaman Karawo SME’s in Gorontalo (Journal of Pharmaceutical Negative Results, 2022)
Aim: The purpose of this study to measure and analyze influence entrepreneurship orientation toward market orientation and aesthetics innovation, entrepreneurship orientation toward business performance, market orientation towards business performance SME’s, aesthetics innovation toward business performance, entrepreneurship orientation toward business performance mediated by market orientation and entrepreneurship orientation toward performance business, mediated aesthetics innovation in Small and Medium Enterprises (SMEs) sulaman karawao in Gorontalo. Methods: Object study is an Sulaman Karawo SME’s in Gorontalo. The type of data is primary data. Amount population are 701 SME’s spread across six cities District /City in Gorontalo. The sampling technique is purposive sampling. Analysis tools use Structural Equation Model (SEM) with AMOS 25 software program. Results: Findings results study is enhancement performance SMEs sulaman karawo in Gorontalo is done by direct through entrepreneurship orientation, market orientation and aesthetics innovation and indirect through market orientation and aesthetics innovation.